Cu‐Promoted Pt/Ce0.5Zr0.5Ox Catalyst for Ammonia Production Reaction of Passive SCR from Nitric Oxide and Hydrogen. Issue 2 (12th January 2022) - Liu, Min; Yan, Ruining; Wang, Yinan; Zhao, Xuteng; Dongdong, Guo; Honglin, Cao; Zhan, Reggie; Lin, He
Abstract: In response to stricter emission regulations, lean‐burn engines have attracted more and more attention. However, lean burn engines would inevitably lead to the increase in NOx emissions. The researchers combined Three‐Way Catalyst (TWC) and Selective Catalytic Reduction (SCR) to propose "passive SCR", which makes the engine periodically switch between rich and lean burn. During rich combustion, ammonia is produced by the TWC catalyst, stored in the downstream SCR, and reacts with NOx during lean combustion, in which increasing the ammonia yield on the TWC catalyst is the key. In this study, the self‐propagating high‐temperature synthesis method was used to modify the catalyst by adding copper to improve the ammonia production efficiency. The conversion rate of catalysts with different copper doping ratios from NO to ammonia was measured. Through XRD, BET, H2 ‐TPR, TEM, HRTEM, XPS, in‐situ DRIFTS, etc., the improvement mechanism of copper doping was analysed. The results showed that Pt0.01 Cu0.1 Ce0.45 Zr0.45 Ox had the highest catalytic activity, the widest reaction temperature window (300–550 °C) with the conversion greater than 96 %. The characterization results showed that appropriate amount of copper doping can adjust the valence distribution, form more oxygen vacancies, and improve the distribution of active species. The in‐situ DRIFTS further demonstrated that the conversion from bridged to monodentate and bidentate nitrate may be the key factors on the catalyst surface. Abstract : Different proportions of Cu‐doped Pt0.01 /Ce0.5 Zr0.5 Ox catalysts was synthesized to improve ammonia production activity of three‐way catalysts (TWC). Pt0.01 Cu0.1 Ce0.45 Zr0.45 Ox had the best activity. Appropriate amount of copper doping can adjust the valence distribution, form more oxygen vacancies, and improve the distribution of active species. The conversion from bridged to monodentate and bidentate nitrate may be the key factor on the catalyst.